Melodamide A from Melodorum fruticosum — Quantification using HPLC and one‐step‐isolation by centrifugal partition chromatography. Issue 20 (29th August 2019) - Engels, Nora S.; Waltenberger, Birgit; Schwaiger, Stefan; Huynh, Loi; Tran, Hung; Stuppner, Hermann
Abstract: Melodamide A, a phenolic amide from the leaves of Melodorum fruticosum Lour., has previously shown pronounced anti‐inflammatory activity. In order to rapidly isolate larger quantities for biological testing, a fast, one‐step isolation method by centrifugal partition chromatography was developed within this study. Fractionation of the dichloromethane extract was performed with a two‐phase solvent system consisting of n ‐hexane, ethyl acetate, methanol, and water (3:7:5:5, v/v), leading to the isolation of melodamide A with a purity of >90% and a yield of 6.7 w% within 32 min. The developed method can also be used in dual mode for the enrichment of further constituents like flavonoids or chalcones. In order to support the centrifugal partition chromatography method development, additionally, a high‐performance liquid chromatography method was established and validated to determine quantities of melodamide A in plant material and crude extracts. Analysis of M. fruticosum leaves and a dichloromethane extract obtained from this plant material showed a total melodamide A content of 0.19 ± 0.008 and 8.9 ± 0.249 w%, respectively.